THE PERCUTANEOUS CHEMICAL ABLATION APPLICATION IN THE TREATMENT OF PATIENTS WITH HEPATOCELLULAR CARCINOMA - Levchenko, Lyudmila; Kozachuk, Yelyzaveta; Zemskov, Sergey (The Ukrainian Scientific Medical Youth Journal, 2020)
In the world, the incidence of HCC constantly increases each year. In the period from 1990 to 2015, the rate of newly diagnosed cases of HCC increased by 75%. In Ukraine in 2018, only 18.0% of primary patients were gotten special treatment: 4.9% only by surgery, 2.0% by combined and complex treatment. Unsatisfactory results of special treatment coverage are associated with the peculiarities of the etiopathogenesis of HCC, asymptomatic course, and improper screening system of patients at risk, which leads to difficulty in diagnosis of HCC in the early stages. The choice of HCC treatment tactics, associated with viral hepatitis and liver cirrhosis, remains a difficult clinical chal- lenge. The radical treatment at an early stage HCC is a cornerstone for improving overall survival. Per- cutaneous ablation (PA) was developed for inoperable patients with HCC in the early stages and liver cirrhosis. There are radiofrequency ablation, chemical ablation, cryoablation, microwave ablation, etc. The main indications for the local ablation application are very early and early-stage (according to BCLC - stage 0 and A), compensated or subcompensated liver function in cirrhosis (Child-Pugh class A and B), ECOG 0-1, the diameter of the tumor lesion up to 5.0 cm (most optimally up to 3.0 cm), focal nodal lesion, solitary or multiple lesion. Percutaneous ablation is used as a bridge therapy to local tumor control in patients who undergo the Milan and the UCSFC criteria and are on the waiting list for transplantation. These methods have also shown their effectiveness as neoadjuvant «downstaging» therapy in patients who are not candidates for liver transplantation and/or with initially unresectable lesions. For many decades, percutaneous chemical ablation has been the “gold” standard for mini- mally invasive treatment of HCC. This method is easy to perform, does not require special equip- ment, is well tolerated by patients, safe, and cost-effective. The main chemical agents are ethanol and acetic acid. The percutaneous chemical ablation procedure involves intratumoral administration of a chemical agent a real-time under the control of imaging (ultrasound or CT). Chemical ablation is a second-line method and is used only in cases where there are contraindications to radiofrequency ab- lation. This method is not accompanied by severe specific complications and mortality. The effective- ness of its clinical application directly depends on the size of the tumor. The optimal size of the tumor is not more than 3.0 cm. Intratumoral administration of ethano promotes necrosis of 90% -100% of HCC with a diameter of ≤ 2.0 cm and 70% for tumors with 2.0 - 3.0 cm